Association between CBR and Soil Index Properties: Empirical Analysis from Chitwan and Makwanpur District Soil Samples - Koirala, Dipak; Awasthi, Keshab Datt; Bohara, Niraj (Journal of UTEC Engineering Management, 2023)
DOI: https://doi.org/10.36344/utecem.2023.v01i01.002 The California Bearing Ratio (CBR) value is a crucial soil parameter in road construction and design. Obtaining representative CBR values is challenging, requiring time-consuming and expensive testing procedures. To address this issue, regression equations were developed to establish correlations between CBR and soil index properties. Laboratory tests were conducted to determine the soaked CBR, Liquid Limit (LL), Plastic Limit (PL), Plasticity Index (PI), Maximum Dry Density (MDD), and Optimum Moisture Content (OMC) of soil samples. Regression models were then created between CBR and different sets of soil index properties using Microsoft Excel 2007. Strong correlations were observed between soaked CBR, PL, PI, OMC, and MDD (R2 = 0.744); CBR, LL, PL, OMC, and MDD (R2 = 0.702); CBR, PI, OMC, and MDD (R2 = 0.643); CBR, LL, OMC, and MDD (R2 = 0.621); and CBR, OMC, and MDD (R2 = 0.602). Among all equations, the relation CBR = 0.72 PL – 1.22 PI + 2.34 OMC + 106.97 MDD – 222.46 exhibited the strongest correlation with a P-value of 0.005 and R2 of 0.744.